STANDARDIZATION OF SIMPLICIA AND LIME PEEL EXTRACT - Sari, Wahyunita Yulia; Ramadhan, Muhammad Fauzi; Yuniar, Setyowati Eka; Purwoko, Bambang; Nova, Triyo; Mubarok, Fa'iq Hanif (Poltekkes Kemenkes Surakarta, 2025)
Lime (Citrus aurantifolia Swingle) is one of the plants that can be used as traditional medicine. Parts of the lime plant that can be used as traditional medicine include the fruit, leaves, and peel. Lime peel waste is known to contain chemical compounds and as a raw material for medicine, standardization is needed to ensure its quality. The 70% ethanol extract of lime peel was made using the maceration extraction method. This study aimed to standardize both simplicia and 70% ethanol extract of lime (Citrus aurantifolia Swingle) peel according to the Indonesian Herbal Pharmacopoeia (2017) guidelines to ensure quality for pharmaceutical raw material applications.Lime peel was processed into simplicia and extracted using maceration with 70% ethanol. Standardization was performed on both simplicia and extract based on specific (organoleptic, phytochemical screening) and non-specific parameters (drying loss, water content, total ash, acid-insoluble ash, ethanol-soluble extract, water-soluble extract, and specific gravity). All analyses were performed in triplicate (n = 3) and statistical significance was tested using SPSS version 26 with a confidence level of 95% (p < 0.05).Both simplicia and extract met the pharmacopoeial requirements and can be recommended as standardized raw materials for herbal pharmaceutical formulations. These findings provide a reference for the quality control of herbal raw materials and promote sustainable utilization of lime peel waste.